تنمية مهارات التفكير النقدي والإبداعي لدى الطلاب أساليب تحفيزية وتفاعلية - Amjed Jumaah , Assist. Lect . Lujain (Basra studies journal, 2026)
The current research aims at identifying the impact of using interactive and motivational methods on developing critical and creative thinking skills among secondary school students in Basra Governorate. To achieve the research objectives, a sample of (100) male and female students was selected using a simple random sampling method. They were divided into two equal groups: an experimental group and a control group, with (50) male and female students in each group. The researcher used two tools to collect data: a critical and creative thinking test (pre- and post-test) and a student satisfaction questionnaire with interactive methods. The data were analyzed using a set of statistical methods, such as analysis of variance (ANOVA), the independent sample t-test, and the simple Pearson correlation coefficient. The results showed statistically significant differences in favor of the students in the experimental group who underwent the interactive and motivational methods experiment, as they recorded a 25% improvement compared to a limited improvement of 8.3% among the students in the control group. The satisfaction survey also showed that 85% of students in the experimental group expressed satisfaction with the new teaching methods, compared to only 65% ​​of students in the control group. Also these results confirm the importance of employing interactive and motivational methods in the educational process to support the development of critical and creative thinking among students.